Advokat yang Merintangi Proses Penyidikan Perkara Tindak Pidana Korupsi Dihubungkan dengan UU No 18 Tahun 2003: - Aja Maimuna; Fauziah Lubis (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
An advocate is one of the law enforcers whose job is to provide legal assistance or legal services to the public or clients who are facing legal problems whose very existence is needed by the community (Winarta, 1995). The purpose of this writing is to analyze advocates who hinder the process of investigating corruption cases related to Law No. 18 of 2003 concerning Advocates in the Manatap Ambarita, SH case. The author uses a descriptive analysis method, which is a method of solving actual problems by collecting data, compiling or classifying, explaining and then analyzing. The results of the study show that advocate defendants are prohibited from obstructing various processes of investigation and examination of criminal cases, especially corruption as an extraordinary crime. The actions of an advocate obstructing the process of investigating and examining a criminal act of corruption can be threatened with Article 21 of Law Number 31 of 1999 jo. Law Number 20 of 2001 concerning the Eradication of Corruption Crimes shall be subject to imprisonment for a minimum of 3 (three) years and a maximum of 12 (twelve) years and/or a fine of at least Rp. 150,000,000.00 (one hundred and fifty million rupiahs) and a maximum of Rp. 600,000,000.00 (six hundred million rupiahs) has explained the elements and forms of criminal responsibility for the crime of obstructing the investigation and examination of corruption cases. Keywords: Advocate, Crime, Corruption